PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI IMPLEMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) PADA MATA PELAJARAN MATEMATIKA KELAS V DI UPT SDN 066047 MEDAN HELVETIA - Patri Janson Silaban; Nanda Julfa Rezeki; Novi Khairani Syam; Maulida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics subjects in Elementary Schools are subjects that are often considered difficult by students, resulting in low student learning outcomes. The process of learning mathematics is not just transferring knowledge from teachers to students, but a process to be able to solve more complex problems. This study aims to improve student learning outcomes through the implementation of the Discovery Learning learning model with the Culturally Responsive Teaching (CRT) approach. This type of research is Classroom Action Research (CAR). The study was conducted in two cycles. Based on data analysis, there was an increase in learning outcomes from each cycle, namely in cycle I, learning completion was 75%, and in cycle II there was an increase of 25%, and learning completion became 100%. So with the results achieved, it can be concluded that in learning there was an increase in mathematics learning outcomes in the material of integers for class V students of UPT SDN 066047 Medan Helvetia using the discovery learning model with the culturally responsive teaching (crt) approach.